2016
DOI: 10.1074/jbc.m116.742916
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Foundations of Health and Energy Conservation in Hibernating Free-ranging Subadult Brown Bear Ursus arctos

Abstract: Brown bears (Ursus arctos) hibernate for 5-7 months without eating, drinking, urinating, and defecating at a metabolic rate of only 25% of the summer activity rate. Nonetheless, they emerge healthy and alert in spring. We quantified the biochemical adaptations for hibernation by comparing the proteome, metabolome, and hematological features of blood from hibernating and active free-ranging subadult brown bears with a focus on conservation of health and energy. We found that total plasma protein concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 54 publications
3
59
1
1
Order By: Relevance
“…Again, we consider that better understanding of modulations within the mechanisms of the clotting cascade in black bears may introduce opportunities for employing novel clinical mechanisms for anti-coagulation therapy and targeted treatments. It should be noted that in a very recent publication the clotting behavior in hibernating brown bears (Ursus arctos) has been described to elicit similar responses (Welinder et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Again, we consider that better understanding of modulations within the mechanisms of the clotting cascade in black bears may introduce opportunities for employing novel clinical mechanisms for anti-coagulation therapy and targeted treatments. It should be noted that in a very recent publication the clotting behavior in hibernating brown bears (Ursus arctos) has been described to elicit similar responses (Welinder et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Brown bears hibernate for several months during which they do not eat, drink, defecate or urinate, thus reducing the use of the bladder, kidneys, and digestive tract (Folk, Folk, & Minor, 1972;Hissa, 1997;Stenvinkel, Fröbert, et al, 2013). Hibernation adaptations allow bears to overcome anuria, hyperlipidemia, and immobilization (Welinder et al, 2016), preserve muscles and bones avoiding osteoporosis or sarcopenia (Fröbert, Frøbert, Kindberg, Arnemo, & Overgaard, 2020;Vestergaard et al, 2011) and prevent diseases such as metabolic syndrome, diabetes, and cardiovascular pathologies (Arinell et al, 2012;Fröbert et al, 2020;Nelson & Robbins, 2015). The physiological modifications that occur in bears during hibernation, and which are summarized below, might be the result of ultimate factors such as metabolic dietary-related needs and energy conservation, which brown bears have to deal with to survive the winter (Table 1).…”
Section: Hibernation Physiology and The Potential Energetic Costsmentioning
confidence: 99%
“…The hibernating induction trigger (HIT), a compound present in the blood, might initiate physiological and metabolic changes that lead to hibernation (Hellgren, 1998;Hissa et al, 1994;Jørgensen et al, 2014;Welinder et al, 2016), although it has also been suggested than more than a single substance could trigger all these changes (Hissa, 1997). For example, the sex hormone-binding globulin protein, which increases its concentration 45-fold during hibernation, might also help trigger hibernation (Welinder et al, 2016).…”
Section: Hibernation Physiology and The Potential Energetic Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomes of blood, organs and tissues can be characterised by mass spectrometry (MS), which identifies proteins and determines relative protein quantities by matching the mass of peptide fragments to predicted peptide sequences from databases. The differences between the summer and winter brown bear plasma proteome have been characterised by Welinder et al [30], providing information of the biochemical adaptions for hibernation, as the bloodstream has primary functions in signalling. A number of adaptations specific to hibernation were discovered, including energy conservation by decreased levels of the majority of plasma proteins combined with maintained or moderately increased levels of a few key plasma proteins performing crucial functions in hibernation.…”
Section: A Strategy To Translate From Bears To Humansmentioning
confidence: 99%